Ca2+-activated Cl- channels of the ClCa family express in the cilia of a subset of rat olfactory sensory neurons. - Carolina Gonzalez-Silva; Jorge Vera; María Rosa Bono; Christian González-Billault; Brooke Baxter; Anne Hansen; Robert Lopez; Emily A Gibson; Diego Restrepo; Juan Bacigalupo (PLoS ONE, 2013)
The Ca(2+)-activated Cl(-) channel is considered a key constituent of odor transduction. Odorant binding to a specific receptor in the cilia of olfactory sensory neurons (OSNs) triggers a cAMP cascade that mediates the opening of a cationic cyclic nucleotide-gated channel (CNG), allowing Ca(2+) influx. Ca(2+) ions activate Cl(-) channels, generating a significant Cl(-) efflux, with a large contribution to the receptor potential. The Anoctamin 2 channel (ANO2) is a major constituent of the Cl(-) conductance, but its knock-out has no impairment of behavior and only slightly reduces field potential odorant responses of the olfactory epithelium. Likely, an additional Ca(2+)-activated Cl(-) channel of unknown molecular identity is also involved. In addition to ANO2, we detected two members of the ClCa family of Ca(2+)-activated Cl(-) channels in the rat olfactory epithelium, ClCa4l and ClCa2. These channels, also expressed in the central nervous system, may correspond to odorant transduction channels. Whole Sprague Dawley olfactory epithelium nested RT-PCR and single OSNs established that the mRNAs of both channels are expressed in OSNs. Real time RT-PCR and full length sequencing of amplified ClCa expressed in rat olfactory epithelium indicated that ClCa4l is the most abundant. Immunoblotting with an antibody recognizing both channels revealed immunoreactivity in the ciliary membrane. Immunochemistry of olfactory epithelium and OSNs confirmed their ciliary presence in a subset of olfactory sensory neurons. The evidence suggests that ClCa4l and ClCa2 might play a role in odorant transduction in rat olfactory cilia.